Assessing the environmental impacts of wildlife television programmes. Issue 6 (12th August 2021) - Aitchison, John; Aitchison, Rowan; Devas, Fredi
Abstract: Wildlife TV programmes reach very large global audiences, but it is hard to measure their benefits for the natural world. The commercial need to entertain as well as inform means that many films omit the presence and impacts of people, giving the false impression that we do not affect the natural world. Many wildlife film‐makers want to address the linked climate and biodiversity emergencies, but the obligation to be impartial has made some broadcasters reluctant to commission and show films that seek to change people's behaviour. Internet video streaming services are less constrained, but commercial considerations do apply. Privately funded programmes need not be commercially successful or editorially impartial. They can be distributed over the internet, independently of broadcasters. Increasingly, impact producers are being employed as key components in wider campaigns, to maximise their effect. Mainstream TV companies are starting to follow. Making international wildlife programmes entails a large carbon footprint, much of it due to travel. Many broadcasters and production companies are committing to become carbon‐neutral. Programme‐makers would welcome research that helps them maximise the real‐world impacts of their films and quantifies positive changes for nature. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.